Mecca Al-Mukarramah and its development during the reign of Sultan Suleiman the Magnificent (1520–1566 CE): An analytical study based on the Ottoman Daftar al-Mahāmm - Zahir, Ehab Mohammad; Al-Omoush, Anas Nayef (Research Journal in Advanced Humanities, 2026)
This study aims to demonstrate that the reign of Sultan Suleiman the Magnificent (1520–1566 CE) marked a decisive shift in Mecca’s governance from symbolic suzerainty to a systematized religio-imperial administration. Drawing on Ottoman archival sources, particularly the Daftar al-Maḥāmm (Registers of Imperial Decrees), it reconstructs how Mecca was integrated into the Ottoman administrative framework through decrees regulating pilgrimage logistics, fiscal endowments, and Sharifian authority. The findings reveal Suleiman’s interventions in curbing corruption among Egyptian pilgrimage commanders, financing major urban projects such as the ʿAyn ʿArafah water canal and public housing, and standardizing the judiciary to ensure accountability. These reforms transformed the Hijaz from a peripheral sanctuary into a governed province, balancing Ottoman central control with local elites. The study concludes that this structured governance reinforced the Sultan’s legitimacy as Khādim al-Ḥaramayn al-Sharīfayn and established a foundational model for uniting religious authority with bureaucratic centralization in early modern Islamic rule.